Effects of management regimes on growth attributes and carbon density in tropical forests - Richard, Aldrich (2023)
Understanding the effect of management regimes on the long-term growth attributes and carbon density in tropical forests is essential in ensuring a sustained timber yield and safeguarding their role as carbon sinks to combat climate change. Previous studies have shown that logged-over tropical forests were not regenerating according to the Selective Management System’s assumption. These findings were based on short-term data growth, a single study site and censuses carried out after extreme drought events. Thirty longterm permanent sample plots with a total size of 30 ha were analysed to understand the effect of Selective Management System regimes and the actual growth rate of logged-over forests. The perturbation of extreme drought events was also evaluated to understand the effect of climate change. These permanent sample plots were managed under three regimes: unlogged, moderately logged (all Dipterocarp > 65 cm and Non-dipterocarps >60 cm dbh logged) and intensely logged (all Dipterocarps > 50 cm and Non-dipterocarps >45 cm dbh logged). The plots were allowed to regenerate naturally without any silvicultural treatments carried out post-logging. The growth attributes used for this study were mortality, recruitment, stem density, basal area, timber volume and aboveground carbon density. The results showed no significant differences between moderately (772.85 stems ha-1; 52.38 m3 ha-1; 87.38 tonnes C ha-1) and intensely logged forests (665.22 stems ha-1; 25.61 m3 ha-1; 58.36 tonnes C ha-1) in forest stem density, timber volume and aboveground carbon density one year post-logging. Both logged forests showed a significant difference from unlogged forests (1,192.15 stems ha-1; 219.93 m3 ha-1; 228.35 tonnes C ha-1). Only basal area was significantly different between unlogged, moderately logged and intensely logged at 36.71 m2 ha-1, 16.64 m2 ha-1 and 11.96 m2 ha-1, respectively. Annual mortality and recruitment rate were also significantly different between unlogged forests (1.8% yr-1; 0.5% yr-1) compared to the moderately logged (4.0% yr-1; 2.1% yr-1) and intensely logged (3.9% yr-1; 2.1% yr-1) forest. Thirty years post-logging, the intensely logged regime had a higher growth rate, especially for forest stem density (-9.54 stems ha-1 yr-1), basal area (0.22 m2 ha-1 yr-1), timber volume (1.85 m3 ha-1 yr-1) and aboveground carbon density (1.65 tonnes C ha-1 yr-1) compared to moderately logged (-12.91 stems ha-1 yr-1; 0.12 m2 ha-1 yr-1;1.47 m3 ha-1 yr-1; 1.16 tonnes C ha-1 yr-1) and unlogged (-15.09 stems ha-1; 0.02 m2 ha-1 yr-1; 1.18 m3 ha-1 yr-1; 0.57 tonnes C ha-1 yr-1) forests. The actual recovery growth of timber volume (1.47 - 1.85 m3 ha-1 yr-1) and aboveground carbon density (1.16 – 1.65 tonnes C ha-1 yr-1) for logged forests were below the national average and required more than 30 years to recover to the pre-logging status. The extreme drought threshold of -1.70 midterm Standardized Precipitation Evapotranspiration Index impacted tropical forest growth and frequently occurred from 1990-2019. The extreme drought increased the mortality rate (4.0% yr-1) and decreased the recruitment (1.8 % yr-1), forests stem density (-17.95 stems ha-1 yr-1), basal area (0.17 m2 ha-1 yr-1) and aboveground carbon density (1.6 tonnes C ha-1 yr-1) in logged forests. The unlogged forests were affected by extreme drought by increased mortality (3.5% yr-1), recruitment (8.9% yr-1), stem density (60.09 stems ha-1 yr-1) and basal area (0.62 m2 ha-1 yr- 1) but decreased timber volume (-1.3 m3 ha-1 yr-1). Enhancing current practices such as longer cutting cycles, dipterocarps and non-dipterocarps tree species volume control, enrichment planting and climbers cutting, in addition to practising Reduced Impact Logging, will reduce the impact of logging and improve the growth and recovery rate of logged-over forests.